Dynamics of India’s Contemporary Domestic Security Challenges - A.Z. Hilali (Journal of Political Studies, 2017)
India’s immense diversity is unique with its pluralism based on myriad ethnic communities, cultures, religious identities and tribes. Since independence, the country failed to produce one single dominant nation’s concept because identities have not yet forged a common national outlook and its ethnic, religious, and cultural identities remains strong and quite distinctive. Moreover, the Indian federal structure seems to be failed to accommodate the expectations of diverse communities and socio-political cultures. Consequently, the federation is asymmetric with the separatist movements in many parts of the country specifically violent movements in Kashmir, Nagaland, Assam, Manipur and Mezoland which have severely challenged the country’s sovereignty. Furthermore, the insurgencies in Northeast of India and violent movements of Naxalites and Maoist have also challenged India’s territorial integrity. In the same manner the Dalits (Harijan) and minorities (Christians and Muslims), are the victims of superior Hindu caste and Hindu chauvinism. Hence it is perceived that India has lost sight of vital constitutional spirit of secularism and federalism. Further, the worst internal security situation lies on India’s unfair, unbalanced and discriminatory policies with the communities and especially with its judicial system. Nonetheless, it has proved that various socio-economic and political imperatives are not fulfilled by the ruling elites or society. Thus, ethno-religiousideological fault lines, which exist in India, have to be managed with a sense of fairness and transparent federal policies and there is no need to use forces to suppress people. In this context, India requires peaceful and development manual at the national level in order to stabilize all section of society. Without a coordinate approach, the domestic security threats will lead the country to the worst situation.